Effection of Some MicroRNAs Related to Cell Death to Eight-Week Resistance Training in Women with Breast Cancer - mohsen Akbarpour; Fazlolllah fatollahi shourabeh; Mahya Hamidi (Fasa University of Medical Sciences, 2020)
Background & Objective: Breast cancer is the most common cancer in women and is the leading cause of death from cancer among women. The purpose of this study was to evaluate the compatibility of some of the microRNAs associated with cell death to resistance training in women with breast cancer. Materials & Methods: Twenty women with breast cancer were selected randomly. They were randomly divided into control (10) and experimental (10 subjects) groups. Experimental group performed 3 sessions of resistance training for 8 weeks and weekly with the intensity of 70-50% had at most one maximum repetition. In order to investigate the effect of resistance training on mir-329, mir-15, mir-16, blood samples of the subjects were taken 48 hours before and after protocol implementation. Data were analyzed using SPSS software (version 19) and independent and dependent t tests were performed. P value less than 0.05 was considered significant.                Results: Eight resistance exercises have increased the number of cell deaths associated with cell death in women with breast cancer, resulting in increased cell death and, consequently, reduced cancer mass in women with breast cancer. Conclusion: Eight resistance exercises lead to an increase in certain cell deaths associated with cell death in women with breast cancer, resulting in increased cell death and, consequently, a reduction in cancer mass in women with breast cancer.